Companion Proceedings of the 36th International Conference on Software Engineering 2014
DOI: 10.1145/2591062.2591167
|View full text |Cite
|
Sign up to set email alerts
|

Scenario-based programming: reducing the cognitive load, fostering abstract thinking

Abstract: We examine how students work in scenario-based and objectoriented programming (OOP) languages, and qualitatively analyze the use of abstraction through the prism of the differences between the paradigms. The findings indicate that when working in a scenario-based language, programmers think on a higher level of abstraction than when working with OOP languages. This is explained by other findings, which suggest how the declarative, incremental nature of scenario-based programming facilitates separation of conce… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
20
0

Year Published

2014
2014
2024
2024

Publication Types

Select...
4
3
2

Relationship

3
6

Authors

Journals

citations
Cited by 64 publications
(20 citation statements)
references
References 36 publications
0
20
0
Order By: Relevance
“…Consequently, Students enjoy the learning experience; feel motivated and ready for more improvement, in the other side, the teacher found more time to go further on the course [7]. To elaborate collaborative learning in teaching programming for lab sessions, it is necessary to design a collaborative strategy for each step in problemsolving and hire metacognitive abilities respectively in every simple activity [8]. Based on this idea, the students' final program is the result of a collaborative strategy in teaching programming lab sessions starting from forming adequate groups which students work and learn from sharing, discussing their separated solutions and select the best solution that everyone has participated and understood.…”
Section: Introductionmentioning
confidence: 99%
“…Consequently, Students enjoy the learning experience; feel motivated and ready for more improvement, in the other side, the teacher found more time to go further on the course [7]. To elaborate collaborative learning in teaching programming for lab sessions, it is necessary to design a collaborative strategy for each step in problemsolving and hire metacognitive abilities respectively in every simple activity [8]. Based on this idea, the students' final program is the result of a collaborative strategy in teaching programming lab sessions starting from forming adequate groups which students work and learn from sharing, discussing their separated solutions and select the best solution that everyone has participated and understood.…”
Section: Introductionmentioning
confidence: 99%
“…This sentiment is echoed by a number of studies with emerging evidence that some of the more difficult concepts such as initialisation, variables and loops need to be explicitly taught [11,12,20]. Other studies raise the need for learners' cognitive load to be managed by more closely controlling learning opportunities and learning experiences [1,32,33]. This research has implications for pedagogy in school, suggesting that targeted teaching is needed for difficult concepts within a controlled progression of learning experiences [35].…”
Section: Teaching Programming: Instructional Approachesmentioning
confidence: 99%
“…The study that was conducted on par with the teaching of the high school course indicates that teaching high-level programming with LSC might have another positive effect, which is encouraging abstract thinking [Alexandron et al 2013b]. A main characteristic of system-level development is dealing with high-level abstraction.…”
Section: Implications To Pedagogymentioning
confidence: 99%
“…The feasibility of this approach was examined in a pilot course on LSC that was given to high school students and followed the course described in the current study, as well as in several courses given to graduate computer science (CS) students. The research conducted on par with the teaching process suggested that high school and graduate students can reach a significant understanding of LSC [Alexandron et al 2013a], and that when using it, students exhibit patterns of high-level thinking [Alexandron et al 2013b]. Undoubtedly, implementing this approach in a larger scale requires further study.…”
Section: Introductionmentioning
confidence: 99%